Life-Cycle assessment of municipal Solid waste in selected landfills in Ibadan (2015)
Increased municipal solid waste generation due to rapid urbanization of Africa cities is contributing to global warming. Life-cycle assessment of municipal solid waste was carried out in two selected landfills in Ibadan, Nigeria. The environmental impact index of Global Warming Potential (GWPIOO) for two waste management scenarios: landfill and incineration were evaluated using GaBi6 package. Biodegradable components of the MS W constitute approximately 47%. The GWP for landfilling and incineration are 24.33 and 15.20 kg (C02-equivalent) respectively. In order to reduce global warming impact, incineration waste management technique is preferred to landfilling in the area of study. The methane gas emitted from landfilling could be tapped as alternative energy source for small and medium enterprises in the locality.